Quarantine vs vaccination : a simulation study - Chan, Pearlie Xin Hong (2017)
In the recent years, infectious diseases like Severe Acute Respiratory Syndrome (SARS), Influenza A (H1N1) and Middle East Respiratory Syndrome (MERS) have affected the world massively. Often, individuals who have been in contact with infected individuals are either vaccinated or quarantined so as to contain the spreading of these infectious diseases.